Risk Factors Associated With Complications in Treated Mandibular Fractures: A Retrospective Cohort Study - Rose, Jamie; Rojas, Edwin M.; Broadie, Jameela; Ma, Boyu; Sittitavornwong, Somsak (Journal of oral and maxillofacial surgery, 2025)
Identifying factors associated with complications in the management of mandibular trauma may improve clinical decision-making. The purpose of this study was to identify risk factors associated with complications in management of mandible factures. We conducted a retrospective cohort study of participants treated at the University of Alabama at Brimingham for mandibular trauma from 2016 to 2023. Subjects under 20 years old and those with lack of follow-up were excluded. The independent variable is a set of risk factors including exposure to tobacco, alcohol, marijuana, other illicit substances, and number of substances. The main outcome variable was the presence of a major complication in the management of mandible fractures. Major complications included sequalae requiring hospitalization or further surgical intervention. The covariate variables collected were demographics, injury characteristics, and treatment modality. Descriptive statistics were used to compare average age among groups. Student's t-test, Fisher's exact test, and the Koopman asymptotic score were used for contingency table analyses. Binomial logistic regression models, adjusted to age, sex, and race, were fit to compute the adjusted odds ratio for having a complication from an independent variable. Statistical significance was set at a P value < .05. Statistical analyses were performed on GraphPad Prism 10.4.1. The study sample was composed of 260 subjects who met the inclusion/exclusion criteria. The ratio of males to females was 4:1 with an average age of 42.3 (±15.7) years. The overall complication rate was 8.5%. The presence of tobacco use and illicit substance use were associated with post-treatment complications risk ratio 3.65, 95% confidence interval: (1.2 to 11.4), P = .02; risk ratio 3.69, 95% confidence interval: (1.6 to 8.0), P = .009, respectively. The use of no substances was associated with fewer post-treatment complications (P = .006). Tobacco use and illicit substance use were associated with higher complication rates in the management of mandibular fractures. Refrainment from substance use in general was associated with fewer complications. Surgeons may use this information to guide clinical decision-making and discussions of consent when counseling patients with these injuries.